Potential of Squid Ink Compounds as Insilicate FabH Protein In Silico - Angelinus Vincentius; Yohanes Bare (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Tuberculosis (TB) is a disease with the second number of cases in Indonesia. The therapy process is carried out by utilizing one of the waste materials, namely squid ink bags, which are predicted to have active compounds. In the TB cycle, the enzyme FabH is catalyzed as a mediator of lipid synthesis. Inhibition of FabH became the main target through the role of squid ink compounds. The squid ink has a potential as bactery inhibitor. The purpose of this study was to analyze the potential of squid ink as an alternative to TB therapy by inhibiting lipid synthesis (FabH). In silico approach was used in this research. Bioactive compound 5,6-dihydroxyindole-2-carboxylic acid (DHICA) (CID: 119405), cinnamic acid (CID: 444539), betaine (CID: 247) were downloaded from PubChem, and FabH protein (PDB ID 2QO1) was downloaded from the protein data bank database. (GDP). Docking used HeX 8.0.0.0, visualization and analysis using Discovery studio ver 21.1.1. Results from the analysis, we found compounds 5,6-dihydroxyindole-2-carboxylic acid (DHICA), cinnamic acid, betaine contained in squid ink molecularly have potential as an alternative TB therapy by inhibiting FabH, the interaction lead to treatment the TB. In vitro and in vivo studies are needed to analyze further before human studies.